Erosive Hand Osteoarthritis: Incidence and Predictive Characteristics Among Participants in the Osteoarthritis Initiative. Issue 11 (28th September 2021) - McAlindon, Timothy E.; Driban, Jeffrey B.; Roberts, Mary B.; Duryea, Jeffrey; Haugen, Ida K.; Schaefer, Lena F.; Smith, Stacy E.; Mathiessen, Alexander; Eaton, Charles
Abstract : Objective: To evaluate age, sex, race, osteoarthritis (OA) severity, metabolic factors, and bone health as risk factors for erosive hand OA at baseline and its incidence over a 48‐month period. Methods: This was a longitudinal cohort study that included participants from the Osteoarthritis Initiative (OAI) with complete hand radiographs from baseline and 48‐month visits who were eligible at baseline for incident erosive hand OA (i.e., had or were at risk for knee OA [criterion for OAI inclusion] and did not currently have erosive hand OA). Individuals were classified as having erosive hand OA if the Kellgren/Lawrence (K/L) grade was ≥2 in at least 1 interphalangeal joint on 2 different fingers and central erosion was present in at least 1 joint. Results: Of the 3, 365 individuals without prevalent erosive hand OA at baseline, 86 (2.6%) developed erosive hand OA during the 48‐month period. Risk factors included older age (relative risk [RR] per SD 1.63 [95% confidence interval 1.35–1.97]), female sex (RR 2.47 [95% confidence interval 1.52–4.02]), greater OA severity (sum K/L grade 13.9 versus 5.3; P < 0.001), and less cortical width (1.38 mm versus 1.52 mm; P < 0.001). After 48 months, subjects who had developed erosive hand OA were characterized by greater progression of radiographic OA (i.e., joint space narrowing, K/L grade progression [RR 1.35], and loss of cortical thickness [RR 1.23]), adjusted for age, sex, race, body mass index, and baseline OA severity (sum K/L grade). Conclusion: These findings demonstrate that erosive hand OA is more common in older women and is strongly associated with severity of articular structural damage and its progression. Individuals who develop erosive hand OA have thinner bones prior to erosive hand OA development and as it progresses, suggesting that erosive hand OA is a disorder of skeletal frailty.